Effects of motor–generator pair system on improving inertial response and primary frequency regulation capability of renewable energy. Issue 2 (12th January 2021) - Gu, Yujun; Huang, Yongzhang; Li, Chenyang; Guan, Fei; Fu, Wenqi; Zhan, Yang; Zhao, Haisen
Abstract: The increasing penetration of renewable energy leads to the decrease of inertia and damping for replacing conventional power plants. The motor–generator pair (MGP) is proposed to improve inertial response and frequency regulation capability for the renewable energy. First, the mathematical model of the MGP and the control method of DC‐link voltage are given. Then, the inertial characteristics of the MGP are analysed, and a mass block is designed by analysing the key factor affecting the moment of inertia. The transient processes in two machines are discussed by comparing the variations of the voltage and current vectors. It turns out that the electromagnetic–mechanical coupling is the key to realise the primary frequency regulation without frequency acquisition. The photovoltaic (PV) is chosen to illustrate the mechanism of achieving a better primary frequency response with DC‐link voltage control methods based on the de‐loading and additional frequency deviation strategies. A grid‐scale simulation model is built to verify the effectiveness of the proposed scheme. Furthermore, six groups of experiments are designed and performed on an experimental bench. The simulation and experimental results demonstrate that the inertial response and primary frequency response of PV can be improved effectively by adopting MGP for grid connection.